Improving Practice Teaching in Primary Schools for School Internship Programme - Khalil, Sumbul (Voices of Teachers and Teacher Educators, 2020)
Today, school education has shifted from being teacher centric to child centric. This has prompted a change in the role of teachers to that of a friend, facilitator and guide. With a change in role of the teacher, the Teacher Education Programmes have also been restructured. In the light of the NCTE Regulations 2014, the field of Teacher Education is presented with many challenges like quality of teachers, preparing the teachers for inclusive classrooms, implementation of ICT in learning, gender issues etc. The School Internship Programme forms an essential part of the pre-service teacher education. The aim of this paper is to suggest strategies for making teaching practice for school internship more effective and divided in three phases i.e., Pre internship phase, Interactive Phase and Post Internship Phase. These strategies would help in improving practice teaching and developing the professional skills desired by the changed school system.